2021
DOI: 10.3390/ma14051260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Smeared Constitutive Laws for Tensile Concrete to Predict the Cracking of RC Beams under Torsion with Smeared Truss Model

Abstract: In this study, the Generalized Softened Variable Angle Truss-Model (GSVATM) is used to predict the response of reinforced concrete (RC) beams under torsion at the early loading stages, namely the transition from the uncracked to the cracked stage. Being a 3-dimensional smeared truss model, the GSVATM must incorporate smeared constitutive laws for the materials, namely for the tensile concrete. Different smeared constitutive laws for tensile concrete can be found in the literature, which could lead to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In many instances, reinforced concrete (RC) beams in buildings and other structures are subject to complex loading including shear, bending, and torsion. Well known analytical approaches such as the softened truss model (Hsu and Mo, 1985; Hsu, 1993; Jeng and Hsu, 2009; Teixeira and Bernardo, 2021) or modified compression field theory (Mitchell and Collins, 1974; Rahal, 2021; Vecchio and Collins, 1986) are able to account for such complex loading and provide adequate bases for the design of new construction. However, for existing structural members requiring repair or strengthening to mitigate deterioration, and/or to increase capacity, existing literature does not provide sufficient experimental data or an analytical approach to designing the strengthening measures, particularly for torsional loads.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, reinforced concrete (RC) beams in buildings and other structures are subject to complex loading including shear, bending, and torsion. Well known analytical approaches such as the softened truss model (Hsu and Mo, 1985; Hsu, 1993; Jeng and Hsu, 2009; Teixeira and Bernardo, 2021) or modified compression field theory (Mitchell and Collins, 1974; Rahal, 2021; Vecchio and Collins, 1986) are able to account for such complex loading and provide adequate bases for the design of new construction. However, for existing structural members requiring repair or strengthening to mitigate deterioration, and/or to increase capacity, existing literature does not provide sufficient experimental data or an analytical approach to designing the strengthening measures, particularly for torsional loads.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that the accuracy of the proposed equations is superior to that of alternative code-based formulations. The torsional behavior of RC beams, with particular attention to the transition from the uncracked to the cracked stage, was also investigated by Teixeira and Bernardo [ 11 ] through the generalized softened variable angle truss-model (GSVATM). The GSVATM was used to check the accuracy of some smeared constitutive laws for tensile concrete proposed in the literature.…”
mentioning
confidence: 99%